Food Borne Disease and the Lifestyles of the Students and Food Handlers in Rural Schools: A Preliminary Observation - Song Jing, Ling; Zamri, Hassan; Regina Garai, Abdullah (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2021)
Food borne diseases cause millions of deaths every year around the world. The major factors contributing to food borne diseases and the prevalence of food poisoning among students are the food preparation process, lifestyles, physical cleanliness and water supplies. Food mismanagement by food handlers and students’ and food handlers’ poor knowledge of food hygiene are the factors that lead to food poisoning among school students. The objectives of this study are to: investigate how food handlers carry out food preparation; determine students’ and handlers’ standards of food hygiene assess the physical cleanliness of school canteens and the purity of their water supplies; and develop guidelines for the prevention of food poisoning. The aspects investigated in this study are the food preparation process, knowledge of food hygiene, physical cleanliness and food poisoning prevention methods.